Description of Character Shift of Nursing Students During the Covid-19 Pandemic Era: A Review - Edison Kabak; Yoel Halitopo; Nuriati Sarlota Auparai; Noor Hadi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The Covid-19 pandemic, directly or indirectly, according to many studies has proven to have caused a shift in the character of nursing students. The purpose of this study is to identify the types of nursing students’ character shifts that occurred during the Covid-19 pandemic and how to manage them. The implication of this study is to contribute the management of handling a shift in the character of nursing students during the pandemic. This study used a document review and was supported with the PRISMA Analysis. The document was screened from 1,583,100 records in the Google search engine. The core documents were filtered through Google Scholar, PubMed, Semantic Scholar, and Other Sources. The keywords used for the search include management, nursing education, character shift, nursing students, and the Covid-19 pandemic. The PRISMA Analysis design provides indicators to be more focused in the search that includes respondents’ character shift, research methods (quantitative), research quality, surveys, document reviews, publication year (2020-2021), results (the focus of shifting character of nursing students during the Covid-19 pandemic), and the language (English). This study review was supported by the PICOT (Population, Intervention, Comparison, Outcome, and Time) model as the instrument to help the screening for quality records. Results showed the total documents out of 1.583.100 records, 108 records were screened, and 21 records were eligible (n=21) that met the requirements for review, i.e. from Google Scholar (n=8), PubMed (n=5), Semantic Scholar (n=4), and Other Sources (n=4). The study conclusion suggested the need for a character shift program for nursing students during the Covid-19 pandemic. The problems that have been found in the 21 review documents of character shifts in nursing students are mental/psychological shifts, shifts in learning/learning methods, shifts in attitudes, and shifts in lifestyle. The results of this study showed there were 15 journals that met the criteria for PRISMA analysis and 100% of the PICOT model in which they also indicated that there were shifting of nursing students’ characters during the covid-19 pandemic